Personalitas Perusahaan Multinasional dalam Hukum Internasional - Syukri, Syukri; Kusniati, Retno (Faculty of Law, Universitas Jambi, 2020)
This article aims to find out and analyze the personality and responsibilities of multinational cooperation in international law. The type of research is normative studies by using statutory, conceptual and historical approaches. It is shown that the personality of multinational cooperation in international law is limited as a quasi subject of international law, which is applied in the context of: 1) party in the settlement of international disputes, limited to the cases of investment disputes through, international arbitration; and 2) party in the drafting of investment contracts using the principles of international trade law, in particular the principles of National Treatment and Most Favored Nations. The responsibilities of multinational cooperation in international law are based on soft law provisions yet applied through host country as the intermediary actor by the regulation in national legal provisions.